PENYESUAIAN DIRI DI LINGKUNGAN SEKOLAH PADA SISWA KELAS XI SMA PASUNDAN 2 BANDUNG - Sulisworo Kusdiyati; Lilim Halimah; Faisaluddin Faisaluddin (HUMANITAS: Indonesian Psychological Journal, 2011)
The purpose of this study is to obtain empirical data about the pictureof adjustment at class XIÂ  Pasundan high school 2. The methodology inthis research used descriptive study. The population of this study was 340students in grade XI and the samples were 181 students. The sampleswere taken used cluster random sampling technique by looking at theKrejcie table. Collecting data used adjustment scale developed byresearchers based on the theory of adjustment from Schneiders. Data wereobtained in the form of ordinal data and analyzed using the median andPercentage (%). The results showed that as many as 86 students (47.5%)could be well adjusted, and 95 students (52.5%) could not be well adjusted.In addition the result showed that students with authoritative parenting andwere not influenced by peers is the most well adjusted.